Using the Work of Internal Auditors in the Assessment of the Business Entity’s Ability for Doing Business as a Going Concern - Selishchev, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article explores and systematizes the strategic aspects of the methodology of using the work of internal auditors when assessing the entity’s ability for doing business as a going concern. The main principles of the internal auditors’ work are formulated. Methodological and methodological approaches to the direct use of the internal audit of a business entity during the conduct of procedures to determine the adequacy of the use of the going concern principle by management personnel when preparing financial statements are further elaborated. Studies devoted to assessing the risk of activity termination in conducting external audit procedures using the results of internal audit or the internal audit work can significantly reduce the scopes of audit procedures without affecting their quality. The assessment of the application of the going concern principle as one of the key phases of the audit, in particular in the aspect of internal audit, requires further consideration and adaptation to current practice. The purpose of the article is to study and develop methodological and methodological approaches to use of internal auditors’ work in assessing the entity’s ability for doing business as a going concern. A characteristic feature of the audit of doing business as a going concern is large scopes of information and issues that need to be investigated separately or jointly in order to adequately assess the appropriateness of applying the assessment of the entity’s ability for doing business as a going concern by management personnel, which requires the use of the work of internal auditors when assessing the entity’s ability for doing business as a going concern. It is argued that the recommendations on the use of internal audit work in the aspect of testing going concern, provided by international auditing standards, require clarification of the task statement and the nature of work that can be done with internal audit.